Bioefficacy of insecticides against Thrips palmi in cotton (Gossypium hirsutum) - RAO, NAVEEN; GAUR, RAM KARAN; KUMAR, RISHI; SINGH, SATNAM; KAMBOJ, RAJAN (The Indian Journal of Agricultural Sciences, 2022)
Various species of arthropod have been recorded as cotton pests at various stages of its growth as defoliators, tissue borers and sap-suckers, causing considerable yield losses. Among these, thrips are one of the most devastating early-season sucking pests limiting cotton (Gossypium hirsutum L.) productivity directly by feeding and transmitting viruses. So far, scanty information is available on the efficacy of insecticide against thrips in cotton. Thus the present study was carried out at Research farm of CCS HAU, Hisar, Haryana during rainy (kharif) season 2019–20 and 2020–21. The efficacy of 14 label-claimed insecticides against Thrips palmi was evaluated under field and laboratory conditions. Under field conditions, profenofos was the most effective insecticide against thrips at three days after spray, while spinetoram recorded the highest thrips reduction after seven days of spray. The following efficacious chemistries against thrips were fipronil and cypermethrin, whereas flonicamid and buprofezin recorded higher thrips population than other treatments. Under laboratory studies, the leaf dip bioassay was conducted to revalidate the field results, and it was found that profenofos, fipronil and spinetoram were highly effective, causing maximum thrips knockdown, whereas lower mortality was recorded in flonicamid. The study provided baseline data on thrips susceptibility to different insecticides, which can be used to develop an effective management strategy by altering different chemistries to avoid selection pressure.